North Shore Place Names : Kahuku to Kaena - Clark, John R. K., 1946- (Book collections on Project MUSE., 2014)
In North Shore Place Names: Kahuku to Ka'ena, ocean expert John Clark continues his fascinating look at Hawai'i's past as told through the stories hidden in its place names. This time the author takes the reader on a historical tour of the North Shore of O'ahu, from Kahuku (the north point of the island) to Ka'ena (the west point of the island), and uncovers the everyday lives of the residents, especially prior to the plantation era. Similar to his 2011 book, Hawaiian Surfing, to research this book Clark tapped into the Ho'olaupa'i online database (www.nupepa.org): a vast archive of 125,000 pages of Hawaiian-language newspapers published from 1834 to 1948. The author collected an enormous number of references to specific North Shore locations and presents them in an easy-to-use dictionary-style format, which includes original passages in Hawaiian with English translations by Keao NeSmith. Discover these highlights and others in this unique look at O'ahu's North Shore: Letters from the longtime principal of the girls' school that eventually gave Hale'iwa its name. Examples of the clash of cultures between traditional Hawaiian practices and Christianity, as evident in accounts of hula performances. Old-time traffic accidents--one that involved Queen Lili'uokalani when she was trapped by her overturned horse-drawn carriage--and unusual train fatalities. Notices of auctions of Government lands, property trespasses, stolen sheep, and stray horses. An invaluable resource for anyone interested in Hawai'i history and the Hawaiian language, North Shore Place Names brings to life the names, places, and events of the historic North Shore community.